Living with chronic obstructive pulmonary disease with focus on fatigue, health and well-being - Stridsman, Caroline (Luleå tekniska universitet, Omvårdnad, 2013)
The overall aim of this thesis was to describe and evaluate experiences of living with chronic obstructive pulmonary disease (COPD), with focus on fatigue, health and well-being. A mixed method study design was used to reach the overall aim. All studies were based on data from the Obstructive Lung Disease in Northern Sweden (OLIN) COPD study. Papers I (n=1350) and III (n=1089) included participants (aged 35-88 years) with and without a spirometric classification of COPD. Bivariate, multiple logistic regression (I, III), and correlation (III) analyses were performed. Papers II (n=20) and IV (n=10) included participants (aged 59-77 years) with moderate to very severe COPD. Semi-structured interviews were conducted, and data were analysed through qualitative content analysis. The result showed that fatigue was worse among people with COPD compared to people without COPD. Fatigue increased with disease severity, and was already worse in COPD grade I among people with respiratory symptoms compared with the non-COPD group. COPD grade II with respiratory symptoms (OR 1.65) and grade III-IV with respiratory symptoms (OR 2.66) were significant risk factors for clinically significant fatigue when adjusted for sex, age, heart disease, and smoking habits (Paper I). Fatigue was described to mainly be COPD related; it was accepted as a natural consequence of COPD, but it was unexpressed. Fatigue affected and controlled the daily life of these people, and with dyspnea, fatigue was described to be overwhelming. Planning physical activity was the most important strategy to manage fatigue (Paper II). Fatigue had a great impact on both physical and mental dimensions of the health status, irrespective of having COPD or not. Among people with clinically significant fatigue, those with COPD had significantly lower physical health scores. Fairly strong correlations existed between FACIT-Fatigue and physical as well as mental health dimensions in SF-36. Increased fatigue and decreased physical and mental dimensions of health, each ...